Pro-inflammatory cytokines and leukocyte integrins associated with chronic neuropathic pain in traumatic and inflammatory neuropathies: Initial observations and hypotheses - Dong, Chaoling; Ubogu, Eroboghene E. (Frontiers in Immunology, 2022)
Leukocyte infiltration and persistence within peripheral nerves have been implicated in chronic nociception pathogenesis in murine peripheral neuropathy models. Endoneurial cytokine and chemokine expression contribute to leukocyte infiltration and maintenance of a pro-inflammatory state that delays peripheral nerve recovery and promotes chronic pain behaviors in these mice. However, there has been a failure to translate murine model data into safe and effective treatments for chronic neuropathic pain in peripheral neuropathy patients, or develop reliable biomarkers that may help diagnose or determine treatment responses in affected patients. Initial work showed that persistent sciatic nerve CD11b+ CD45+ leukocyte infiltration was associated with disease severity in three mouse models of inflammatory and traumatic peripheral neuropathies, implying a direct contributing role in disease pathogenesis. In support of this, CD11b+ leukocytes were also seen in the sural nerve biopsies of chronic neuropathic pain patients with three different peripheral neuropathies. Systemic CD11b antagonism using a validated function-neutralizing monoclonal antibody effectively treated chronic nociception following unilateral sciatic nerve crush injury (a representative traumatic neuropathy model associated with axonal degeneration and increased blood-nerve barrier permeability) and does not cause drug addiction behaviors in adult mice. These data suggest that CD11b could be an effective molecular target for chronic neuropathic pain treatment in inflammatory and traumatic peripheral neuropathies. Despite known murine peripheral neuropathy model limitations, our initial work suggests that early expression of pro-inflammatory cytokines, such as tissue inhibitor of metalloproteinases-1 may predict subsequent chronic nociception development following unilateral sciatic nerve crush injury. Studies aligning animal model investigation with observational data from well-characterized human peripheral neuropathies, including transcriptomics and proteomics, as well as animal model studies using a human clinical trial design should foster the identification of clinically relevant biomarkers and effective targeted treatments with limited addiction potential for chronic neuropathic pain in peripheral neuropathy patients.